CONTROL AND EMOTIONAL REACTIVITY LEVELS: WHICH ONE, POSITIVE OR NEGATIVE EMOTIONAL REACTIVITY, LINKS WITH EFFORTFUL CONTROL? - Hurriyati, Evi Afifah; fitriana, Efi; Cahyadi, Surya; Srisayekti, Wilis (Humaniora, 2020)
The research investigated the relationship between effortful control and emotional reactivity in students. It also analyzed the description of each variable descriptively based on the levels of effortful control and the level of emotional reactivity. The method was by self-report through questionnaires distributed to students aged 18-30 years. There were 357 participants that were consisting of 94 male students and 263 female students. The measuring instrument was the Effortful Control from the Adult Temperament Scale Questionnaire (ATQ) Scale-Short form, and the Perth Emotional Reactivity Scale-Short Form scale. The result shows that there is a positive significant relationship between effortful control and positive emotional reactivity. However, the research shows that there is a negatively significant relationship between effortful control and negative emotional reactivity. It states that students with high levels of effortful control have high positive emotional reactivity. Likewise, students who have low levels of effortful have low positive emotional reactivity. However, individuals who have a high level of effortful control have low negative emotional reactivity and vice versa.